An Effective Method For Removal of Dichromate Ion and Furfural From Aqueous Solutions Using A Nanoporous Adsorbent - ANBIA, MANSOOR; MOHAMMADI, KAVEH (Asian Journal of Chemistry, 2010)
The effect of cationic template on the adsorption of dichromate ion and furfural in MCM-41 was investigated in this work. Cetyltrimethylammonium bromide (CTAB) was used as the cationic template for synthesis of MCM-41 (mobil composition of matter 41, a mesoporous material with a hexagonal array of uniform pores). The properties of synthesized sample were characterized with X-ray diffraction (XRD), FTIR and thermogravimetric analysis. The as-synthesized-MCM-41 samples were used for the separation of dichromate anion and furfural from aqueous solution and showed high adsorption capacity for both of them. The parameters investigated in this study include agitation speed, contact time, composition of adsorbent (in the presence and absence of surfactants) and initial dichromate and furfural concentrations. Adsorption uptakes were rapid on the adsorbent reaching equilibrium in less than 1 h. As-prepared material showed excellent adsorption capacity toward Cr (VI) and furfural (i.e. 2.43 mmol/g and 1.87 mmol/g, respectively). The materials without surfactant does not show affinity for ionic and organic analyte. Dominant sorption mechanisms were predicted to be electrostatic, hydrophobicity, hydrogen bonding and π-π interactions.